What Makes a Pedestrian Path Pleasant? Analysis of Young Pedestrians’ Perceptions - Carmen Forciniti; Laura Eboli (Urban Science, 2023)
In this paper, an analysis of the pedestrian environment based on users’ perceptions is proposed. The specific aim of the study is to discover the aspects mostly influencing the pleasantness of a path in a university campus situated in southern Italy and used by young pedestrians every day to reach various destinations for their university activities. The work is based on data collected by a sample survey and analyzed through a two-step methodology consisting of the application of a Chi-square test and a development of an ordered logit (OL) model. The model results reveal which aspects affect path pleasantness. The specific finding suggests that these aspects relate to the presence of buildings with good facades along the path and to the continuity of the path. As a general and highly relevant finding, we can state that the applied methodology could be very useful in identifying the path characteristics that can be considered as the most important for pedestrians. This identification could support practitioners to plan new strategies and future interventions to improve the pedestrian environment and increase the sense of pleasure perceived by pedestrians.